Landscape of structural variants reveals insights for local adaptations in the Asian corn borer - Yan Peng; Kaikai Mao; Zhuting Zhang; Junfen Ping; Minghui Jin; Xinye Liu; Chao Wu; Chongjun Zhao; Peng Wang; Xueqing Duan; Songmiao Yu; Zhimin Li; et al. (Cell Reports)
Summary: Capturing the genetic diversity of different wild populations is crucial for unraveling the mechanisms of adaptation and establishing links between genome evolution and local adaptation. The Asian corn borer (ACB) moth has undergone natural selection during its adaptative evolution. However, structural variants (SVs), which play significant roles in these adaptation processes, have not been previously identified. Here, we constructed a multi-assembly graph pan-genome to highlight the importance of SVs in local adaptation. Our analysis revealed that the graph pan-genome contained 176.60 Mb (∼37.33%) of unique sequences. Subsequently, we performed an analysis of expression quantitative trait loci (QTLs) to explore the impact of SVs on gene expression regulation. Notably, through QTL mapping analysis, we identified the FTZ-F1 gene as a potential candidate gene associated with the traits of larval development rate. In sum, we explored the impact of SVs on the local adaptation of pests, therefore facilitating accelerated pest management strategies.